Nilai-Nilai Moderasi Beragama Mantan Preman Jamaah Tarekat Syadziliyyah Solo - Warsito, Warsito; Ikhsanudin, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
This study argues that education of Sufism values ​​in the teaching of the Syadziliyyah order is able to form a moderate religious attitude of former thugs in Solo. Humanist and family values ​​make this group of former thugs accept diversity and various Nusantara traditions. Teachings that do not focus on Islamic politics make them accept the 1945 Constitution and Pancasila. They can cooperate with various elements of government from the center to the lowest level. Group activities that show a moderate attitude are activities based on social and personal benefits that include charity and disaster rescue activities by forming team called Juba Rescue. This study is a qualitative study with data collection techniques including interviews, observations and documentation. Determination of respondents using purposive sampling techniques with the criteria of founder, mentor, and active members. Data is analyzed through three stages, namely; data reduction, presentation and drawing conclusions.